2017
DOI: 10.1542/peds.2017-1264
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Very Preterm Infants: An International Comparison of 10 National Neonatal Networks

Abstract: The network ranking of survival rates for very preterm infants remained largely unchanged as GA increased; however, survival rates showed marked variations at lower GAs. The median age at death also varied among networks. These findings warrant further assessment of the representativeness of the study populations, organization of perinatal services, national guidelines, philosophy of care at extreme GAs, and resources used for decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
118
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 35 publications
(35 reference statements)
3
118
1
4
Order By: Relevance
“…However, even among infants admitted with the intention to treat, survival rates can vary markedly. 35 The perinatal interventions studied herein should primarily be looked upon as markers of active management. Some of them (eg, antenatal corticosteroids and centralization of care) rest on a solid base of evidence, 7 whereas others (eg, cesarean delivery and intubation at birth) were chosen to capture the intention to treat among physicians rather than as markers of evidence-based care.…”
Section: Discussionmentioning
confidence: 99%
“…However, even among infants admitted with the intention to treat, survival rates can vary markedly. 35 The perinatal interventions studied herein should primarily be looked upon as markers of active management. Some of them (eg, antenatal corticosteroids and centralization of care) rest on a solid base of evidence, 7 whereas others (eg, cesarean delivery and intubation at birth) were chosen to capture the intention to treat among physicians rather than as markers of evidence-based care.…”
Section: Discussionmentioning
confidence: 99%
“…18 An analysis of data from 10 neonatal networks and a total of 91 835 preterm infants 24-29 weeks of GA indicated that the overall survival rate was 78%-93%. 19 According to the data in this meta-analysis, the survival rate is 64% at week 24 and increases with GA to reach up to 96% at week 29. According to data obtained from 16 regions in Europe, the total mortality rate in weeks 22-31 6 is 27.7%.…”
Section: Discussionmentioning
confidence: 87%
“…The aforementioned meta-analysis encompassing 10 neonatal networks and 91 835 preterm infants at GAs of 24-29 weeks showed the mean time to death was 8 days (4-13 days), with 14% of deaths occurring within the first 24 hours, 29% between days 1-6, 37% between days 7-27 and 23% after day 28. 19 When we evaluated the total number of infants lost in both groups, we found that 14% of the infants died within the first 48 hours, 56% between days 2-7, and 29% after day 7. Deaths within the first 48 hours occur because of immaturity and RDS-associated complications, and can be reduced with RDS prevention and treatment approaches.…”
Section: Discussionmentioning
confidence: 95%
“…The NNRD is also the UK data source for international collaborations. The International Network for Evaluation of Outcomes of Neonates (iNeo) is a quality improvement project based on collaborative comparisons of population-based international healthcare for neonates led by the University of Toronto (http://ineonetwork.org) (28) that has produced a number of outputs (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). eNewborn is a pan-European preterm benchmarking platform (39).…”
Section: Work Supported By the Nnrdmentioning
confidence: 99%